FAKTOR-FAKTOR PENENTU TINGKAT TABUNGAN DI INDONESIA: PENDEKATAN MODEL LIFE CYCLE HYPOTHESIS - Arintoko Arintoko (Optimum: Jurnal Ekonomi dan Pembangunan, 2011)
This study estimates a number of variables hypothesized affect saving rate in Indonesia. These variables such as growth of real income per capita, dependency ratio, interest rate, inflation and lag of saving rate are likely to exert influence on saving rate as suggested by theory and/or prior empirical work. This research employs regression model on time-series data. Research model is based on life cycle hypothesis. It is used to show effect of income growth and population structure on saving rate. Three of five variables used in the model significanly affect saving rate i.e.: real GDP per capita, inflation and lag of saving rate. These variables have positif effect on saving rate. Increasing GDP per capita has impact on increasing national saving rate. Increasing inflation indicates increasing uncertainty motivating households to raise their saving. In addition, there is an inertia of saving rate habit implying that national saving rate in Indonesia would be to exhibit cycle. Thus, saving rate would be increase in the future if there is upwardÂ  trend in prior timeThis study estimates a number of variables hypothesized affect saving rate in Indonesia. These variables such as growth of real income per capita, dependency ratio, interest rate, inflation and lag of saving rate are likely to exert influence on saving rate as suggested by theory and/or prior empirical work. This research employs regression model on time-series data. Research model is based on life cycle hypothesis. It is used to show effect of income growth and population structure on saving rate. Three of five variables used in the model significanly affect saving rate i.e.:real GDP per capita, inflation and lag of saving rate. These variables have positif effect on saving rate. Increasing GDP per capita has impact on increasing national saving rate. Increasing inflation indicates increasing uncertainty motivating households to raise their saving. In addition, there is an inertia of saving rate habit implying that national saving rate in Indonesia would be to exhibit cycle. Thus, saving rate would be increase in the future if there is upwardÂ  trend in prior time